ANALISIS KEBUTUHAN PEGAWAIDI DINAS PEKERJAAN UMUM PROPINSIKALIMANTAN BARAT - Havani E.21109020, Sachril (FISIP Universitas Tanjungpura, 2014)
The problem in this study is non-permanent employees (PTT) in a proactive and innovative work less, work only based on